1998
DOI: 10.1073/pnas.95.25.14920
|View full text |Cite
|
Sign up to set email alerts
|

Tumor cells expressing a retroviral envelope escape immune rejectionin vivo

Abstract: A model system for the in vivo control of tumor cell proliferation by the immune system has been used to assay for the possible immunosuppressive activity of retroviral proteins. Expression vectors for the entire or the transmembrane subunit of the Moloney murine leukemia virus envelope protein were constructed, as well as control vectors for irrelevant transmembrane proteins-or no protein. They were introduced either into MCA205 murine tumor cells, which do not proliferate upon s.c. injection into an allogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
126
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 116 publications
(129 citation statements)
references
References 38 publications
2
126
1
Order By: Relevance
“…During evolution, most of the endogenous retrovirus-derived genes are disrupted by multiple mutational events but occasionally one of them, such as the env gene exemplified here (bottom left), may be preserved and remains functional over several million years, playing a role in the physiology of its host. rstb.royalsocietypublishing.org Phil Trans R Soc B 368: 20120507 further substantiated in our laboratory using in vivo tumour rejection assays that measured the ability of the proteins, when expressed in allogeneic tumour cells normally rejected by engrafted mice, to allow these cells to escape, at least transiently, immune rejection [27]. This approach led to the delineation of the ISD within a 20 amino acid-long peptide and to the identification of two amino acid positions where introduction of specific mutations could abolish the immunosuppressive activity without affecting the fusogenicity and infectivity of the protein [28].…”
Section: The Retroviral Envelope Glycoproteinmentioning
confidence: 92%
“…During evolution, most of the endogenous retrovirus-derived genes are disrupted by multiple mutational events but occasionally one of them, such as the env gene exemplified here (bottom left), may be preserved and remains functional over several million years, playing a role in the physiology of its host. rstb.royalsocietypublishing.org Phil Trans R Soc B 368: 20120507 further substantiated in our laboratory using in vivo tumour rejection assays that measured the ability of the proteins, when expressed in allogeneic tumour cells normally rejected by engrafted mice, to allow these cells to escape, at least transiently, immune rejection [27]. This approach led to the delineation of the ISD within a 20 amino acid-long peptide and to the identification of two amino acid positions where introduction of specific mutations could abolish the immunosuppressive activity without affecting the fusogenicity and infectivity of the protein [28].…”
Section: The Retroviral Envelope Glycoproteinmentioning
confidence: 92%
“…Production of endogenous Env protein may interfere with the normal function of the receptor and can cause cell fusion (32), a dangerous effect even though several env genes have been co-opted for this purpose in the host placenta (33). The transmembrane domain of the Env protein also has immunosuppressive properties (34,35) that might have a negative effect on host fitness. Second, production of endogenous Env protein might be disadvantageous to the ERV, e.g., possibly leading to receptor interference in which intracellular binding of the cellular receptor to endogenously expressed Env protein results in down-regulation of the receptor required for viral reentry (36).…”
Section: Discussionmentioning
confidence: 99%
“…Envelop proteins of HERVs may participate in tumoral processing by enabling tumor cells to escape immune control on account of their immunosuppressive properties. 2,23 Possible HERV involvement in tumor development prompted us to investigate HERV expression in leukemic cells. First, we confirmed that the HERV-K10-like gag gene was transcripted in healthy and leukemia samples.…”
Section: Discussionmentioning
confidence: 99%